Roboethics A Navigating Overview - Tzafestas, Spyros G. (Intelligent Systems, Control and Automation: Science and Engineering,, 2016)
This volume explores the ethical questions that arise in the development, creation and use of robots that are capable of semiautonomous or autonomous decision making and human-like action. It examines how ethical and moral theories can and must be applied to address the complex and critical issues of the application of these intelligent robots in society. Coverage first presents fundamental concepts and provides a general overview of ethics, artificial intelligence and robotics. Next, the book studies all principal ethical applications of robots, namely medical, assistive, socialized and war roboethics. It looks at such issues as robotic surgery, children-robot and elderly-robot therapeutical/social interactions and the use of robots, especially autonomous lethal ones, in warfare. In addition, a chapter also considers Japanese roboethics as well as key intercultural and robot legislation issues. Overall, readers are provided with a thorough investigation into the moralresponsibility (if any) of autonomous robots when doing harm. This volume will serve as an ideal educational source in engineering and robotics courses as well as an introductory reference for researchers in the field.